Nosebleeds in Children as a Potential Marker for Nonaccidental Injury and Serious Underlying Pathology: How Aware Are Hospital Clinicians?. (26th September 2011) - Ismail, Abdul Qader; Gandhi, Anjum
Abstract : Paediatric epistaxis is common and usually of benign origin. However, the differential diagnosis includes serious underlying pathology (e.g., bleeding disorders and blood cancers) and in the very young can be a marker of potential physical abuse. To assess if paediatric and A&E doctors were aware of the important differential, we asked them to complete a Likert scale questionnaire on several different clinical scenarios. Our results show that a significant proportion of doctors of all grades and in both specialties were either not aware of or not concerned about epistaxis in an infant as a possible sign of nonaccidental injury and were not willing to carry out simple blood tests to investigate recurrent nosebleeds in an older child. Our results highlight the need for education and evidence-based guidelines to avoid missing important, if infrequent, causes of paediatric epistaxis, both in the hospital and community setting.